Unemployment and associations with diagnosed health problems in the Norwegian GP-DEP study: a repeated cross-sectional register study (2010–2016) - Øystein Hetlevik; Gunnel Hensing; Ann Kristin Knudsen; Valborg Baste; Inger Haukenes; Tone Smith-Sivertsen; Sabine Ruths (BMJ Public Health)
Introduction While differences in mental health between recipients and non-recipients of unemployment benefits are well known, it is not known whether such differences exist for musculoskeletal and cardiovascular health problems. This study examined the difference in registry-based diagnoses between short term, long term and non-recipients of unemployment benefits in the Norwegian working-age population and further examined if these associations differed by educational level.Methods A cross-sectional repeated register study comprising all working-age individuals (age 21–67 years) with pensionable income in Norway in the period 2010 (N=2 610 956) to 2016 (N=2 791 103). Data were retrieved from the Norwegian population registry, the Education Database, the Database of Social Insurance and the Control and Reimbursement of Health Care Claims Database and linked on individual level. Associations between recipients and non-recipients of unemployment benefits and physician-certified diagnoses were examined with Poisson regression with robust variance estimates (relative risk (RR) with 95% CI) and stratified by education.Results Both short-term and long-term recipients of unemployment benefits were associated with an increased likelihood of having one or more musculoskeletal, psychological or cardiovascular diagnoses compared with non-recipients. The strength of the associations increased with cumulative days of unemployment, with adjusted RRs (95% CIs) for musculoskeletal disorder 1.7 (1.7 to 1.7); psychological diagnoses 2,.2 (2.2 to 2.3); subgroup depression 3.3 (3.2 to 3.3) and for cardiovascular disease 1.3 (1.3 to 1.3) compared with non-recipients. Among highly educated people, the association between unemployment and having a diagnosis was stronger than among unemployed with medium and low education.Conclusions Unemployment benefits recipiency were associated with musculoskeletal, psychological and cardiovascular diagnoses, and the strength of the association increased with higher education. The direction of the relationship could not be determined in this study.